STRENGTHENING MODERATE CHARACTER EDUCATION IN STUDENTS THROUGH ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SABILUR ROSYAD HIGH SCHOOL KARANG MIMBA LARANGAN BADUNG PALENGAAN PAMEKASAN - Mausul, Moh (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze the process of strengthening students' moderate character education through Islamic Religious Education (PAI) subjects at Sabilur Rosyad Junior High School, identify challenges and obstacles faced in its implementation, and provide strategic recommendations to improve the effectiveness of moderate character education in rural schools. Using a qualitative approach with a case study design, this research collected data through in-depth interviews, participatory observation, and document analysis. The research subjects involved PAI teachers, principals, students, and parents to get a comprehensive picture of the practice of moderate character education in the school. The results showed that the strengthening of moderate character in Sabilur Rosyad Junior High School is done through the integration of religious moderation values into the PAI curriculum, the use of interactive learning methods, and religious activities that support the habituation of these values. The main challenges faced include the diversity of student backgrounds, limited educational facilities, and the lack of teacher training related to teaching moderation values. Nevertheless, the implementation of moderate character education has had a positive impact, as seen from changes in students' attitudes that are more tolerant, inclusive, and able to appreciate differences. This study emphasizes the importance of additional support, such as teacher training, the development of moderation-based learning modules, and collaboration between schools and communities, to improve the effectiveness of moderate character education in rural schools.